Providing the necessary type of metal microstructure of titanium and zirconium pipes. - V. A. Tomilo; S. V. Pilipenko (Литьë и металлургия)
The purpose of this work is – providing deformation conditions for obtaining the required texture of pipes made of Ti-3Al-2.5V alloy based on the choice of rational values of the calibration parameters of the t ool – calibers and mandrels during cold pilger rolling of pipes for the required Q-factor distribution along the deformation cone.Purpose of work – providing deformation conditions for obtaining the required texture of pipes made of Ti-3Al-2.5V alloy based on the choice of rational values of the calibration parameters of the tool – calibers and mandrels during cold pilger rolling of pipes for the required Q-factor distribution along the deformation cone. The research methods were based on the existing dependence, which describes the influence of the distribution of true compressions along the deformation cone along the wall thickness and along the average diameter, on the distribution of the Q-factor. Calibration calculation and calculation of all deformation parameters of the Cold Rolling Pipe Process was based on a number of existing theoretical and empirical dependencies included in the generally accepted adapted methods for their calculation.